EFFECT OF ULTRASONIC SRUFACE IMPАСТ MODIFICATION ON THE FATIGUE PROPERTIES OF 316L STAINLESS STEEL - ZHU JiangPei; Ql YuTing; ZHANG ShaoFeng; XU JiaJing; CAO XiaoJian (Jixie qiangdu)
The properties of 316L stainless steel can be improved by using ultrasonie impact method to modify the specimen surface. The fatigue properties and fracture properties of 316 and 316L stainless steel were treated by tensile test, high-cyclefatigue test, SEM, XRD and EDS. The results show that both the tensile strength and the fatigue strength of 316L stainless steel with Iower carbon content are lower. The tensile strength of this austenitic stainless steel can be increased by 19.7%, but the toughness decreased. The fatigue limits of 316, 316L and 316L after impact treatment are 209 MPa, 204 MPa and 254 MPa, respectively. Both of them are about 35% of their tensile strength. The fitting formula of S-N curve is S = -64 + 0.45σb. The fatigue data of 316 with higher carbon content has better normalization, and no side-crack is observed. The fracture surface shows that the cracks initiate from the heterogeneous phase or the non-metallie inclusion. Cracks usually propagate along the grain boundary. The velocity fluctuation of crack propagation zone is also attributed to the heterogeneous phases. After the ultrasonie impact, the rack growth of 316L is obviously reduced, the section fluctuation is larger, and the transient fracture speed is faster.